Uso de um acelerômetro para avaliação de ajustes posturais antecipatórios durante início do passo em pacientes com osteoartrite de joelho - OLIVEIRA, Luana Karine Resende (Universidade Federal do Pará, 2023)
Introduction: Elderly people with severe and moderate levels of Knee Osteoarthritis (OA) have an adaptive strategy to perform gait initiation, which is significantly altered by the level of severity of knee osteoarthritis. In recent years, inertial sensors have been used to assess anticipatory postural adjustments (APAs) for gait initiation, since kinemetry, considered the gold standard, is expensive, difficult to transport, requires calibration and proper installation, becoming its use in clinical settings is unfeasible. There are no studies in the literature that validated the use of accelerometers to assess gait initiation in individuals with Knee OA, nor did they assess their reliability, a fact that reinforces the need for research development in this area with this objective. We also did not find clinical trials in the literature that have evaluated the impact of physiotherapeutic interventions on anticipatory step adjustments. Objective: This project is divided into two studies: Study 1: sought to validate the use of a commercial Metamotion C accelerometer to measure APAs during gait initiation in individuals with Knee Osteoarthritis, as well as to test its reliability. Study 2: will seek to assess whether the use of virtual reality with video game resources, associated with conventional physical therapy treatment, have superior effects on pain, physical capacity, balance and anticipatory postural adjustments in gait initiation in individuals with knee OA. Materials and methods: Study 1: 29 subjects were evaluated using a commercial Metamotion C accelerometer and a camera system – kinemetry with a reflective marker on the lumbar vertebrae and calcaneus. The subjects started the step after the experimenter's random command, and had variables extracted from the protocol: APAlatency, APAamp. Study 2: This is a single-blind, randomized, controlled clinical trial. 40 subjects (31 women and 9 men) were selected and randomized into the TC or VR groups by random allocation (20 in each group). The patients underwent the rehabilitation program for 8 consecutive weeks. An inertial sensor was used during the beginning of the gait to measure the APAs and tests, scales and questionnaires to assess balance, pain and physical capacity. Results: Study 1: there was a statistically significant linear correlation between all variables. The APAlatency variable showed an almost perfect correlation (r = 0.9715; p < 0.00001) and the APAamp variable (r = 0.7358; p < 0.00001) had a strong correlation. The measurements showed high to very high reliability for intraclass correlation for the kinematics and accelerometer amplitude and latency variables. Study 2: The results show that conventional treatment significantly improves pain complaints, physical capacity and balance in individuals with knee AO, but only the group that used associated VR showed improvement in PA parameters. Conclusion: Study 1: Metamotion C is valid and presents high reliability for the evaluation of APAs at step initiation in individuals with knee OA. Study 2: only the group VR showed improvement in APA parameters, demonstrating the importance of using this resource in the rehabilitation of these patients.